1999
DOI: 10.1007/s004410051309
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of nitric oxide synthases in EGF-responsive mouse neural precursor cells

Abstract: Nitric oxide (NO) is a gaseous, radical molecule that plays a role in various physiological processes in the nervous system such as learning and hippocampal plasticity. It is generated from l-arginine by nitric oxide synthases (NOS), which come in three isoforms depending on the tissue of origin, namely inducible-NOS (iNOS in macrophages), endothelial-NOS (eNOS in endothelial cells) and neural-NOS (nNOS in neural cells). We used epidermal growth factor (EGF)-responsive nestin-positive neural precursor cells or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Nitric oxide, mainly produced by enteric neurons and glial cells, causes relaxation of the intestinal smooth muscle in response to nerve stimulation, which is important in gut motility [37,38]. Nitric oxide signaling also regulates proliferation and differentiation of neural precursor cells [39,40]. Although changes in nNOS with NEC have not been reported, there is one report of decreased nNOS expression in a rat model of lipopolysaccharide-induced intestinal injury [41].…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide, mainly produced by enteric neurons and glial cells, causes relaxation of the intestinal smooth muscle in response to nerve stimulation, which is important in gut motility [37,38]. Nitric oxide signaling also regulates proliferation and differentiation of neural precursor cells [39,40]. Although changes in nNOS with NEC have not been reported, there is one report of decreased nNOS expression in a rat model of lipopolysaccharide-induced intestinal injury [41].…”
Section: Discussionmentioning
confidence: 99%
“…23 However, such regulation was not found in other cellular systems. 24 A previous report showed that NO donors inhibited the EGF-induced EGFR transphosphorylation without affecting the binding of the ligand to the receptor. 21 In ovarian carcinoma cells, both exogenously applied NO and endogenously synthesized NO have been shown to inhibit tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nNOS has been shown to be more widely distributed in other types of cells in brain, including astrocytes [20] and neuronal stem cells [21,22] .…”
Section: Chemical Structurementioning
confidence: 99%